Answers

2015-04-30T11:10:24+05:30
y=4^{\log_ex}\iff \log_e x=\log_4y
\iff x=e^{\log_4y}

swap x and y, the inverse function is
y=e^{\log_4x}
1 2 1
2015-05-01T01:35:15+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
y = 4^{log_e x},\ \ \ take\ logarithm\ to\ base\ 4\\\\log_4 y=log_e\ x,\ \ \ x=e^{log_4 y}

It is possible to express x in terms of y, in another way.

log_4 y = log_e x= log_4 x\ *\ log_e 4\\\\log_4 x=\frac{1}{log_e 4}\ log_4 y=log_4 e*log_4\ y=log_4\ y^{log_4 e}\\\\ So\ x = y^{log_4 e}=y^{0.7213..}

y = f(x)  then  x = f⁻¹ (y)        , here f⁻¹ is called the inverse function.

Inverse function is obtained by interchanging x and y, after solving for x.

So inverse function is:
    
y = e^{log_4 x}\ \ \ or,\ \ \ y=x^{log_4 e}=x^{0.7213..}
...
1 5 1
click on thanks button (blue azure color) above please